Интертекст культуры и творчество: направленная «случайность» и открытие - Донская, Е.В. (Культура народов Причерноморья, 2013)
В статье раскрывается процесс обогащения интертекста новыми, представляющими
достижения художественной культуры, текстами, порождающими соответствующие новые
обогащающие образы в образном метаязыке культуры. Этот процесс определяет суть творчества
Ключевые слова: интертекст культуры, творчество, образный метаязык культуры У статті розкривається процес збагачення інтертекста новими, такими, що
представляють досягнення художньої культури, текстами, що породжують відповідні нові збагачуючі
образи в образній метамові культури. Цей процес визначає суть творчості
Ключові слова: інтертекст культури, творчість, образна метамова культури In the article, we consider process of enriching of intertext by creation new, representing
achievements of artistic culture, texts. These texts enrich the pattern meta-language of culture. This process
determines essence of creation.
At consideration of culture as intertext together with pattern meta-language, a creative process is examined as
combining, combination, generation of new images. The «scan-out» of intertext here is certain «accompanying»
process which promotes to create new works of art.
The simple combining of intertext fragments, as a rule, does not result in elite works of art, and generates his
banal standards or kitsch. For an original creative process, which generates aesthetic values, deep senses, and
new images, characteristically, foremost, use of pattern language. Yet not origin, but presentiment of new, not
fully certain defined pattern-theme, results in involuntary extraction semantically similar meta-language
patterns to him. These «produced» patterns are translated in intertext, determining the fragments of intertext,
relevant to the pattern-theme, and now already recombination of these fragments gives reverse translation in the
meta-language of patterns, complementing initial pattern-theme. The pattern completed as a result of the
described process is finally translated by an artist in intertext, «intertwining» the got result in the treasure-house
of culture.
The directed randomness in creation can be examined as heterogeneous translation of the pattern-theme in
intertext, when elements suitable for the creative synthesis is pseudorandom revealed. A creator modifies further,
reconstructs the found fragments of intertext or creates on their basis a new fragment so that finally to realize
pattern-theme.
Opposite to the random selection of fragments of intertext is the direct use of typing canonical, cultural cliché,
standard symbols. Such way doesn’t lead to creative results. We name such «creation» enciphering of
emptiness: there is no pattern of theme, there is no idea, and there will not be a result.
Keywords: Culture intertext, Creation, Pattern meta-language of Culture